Asclepiadaceae endémicas del Perú - León, Blanca (2006)
The Asclepiadaceae are represented in Peru by 27 genera and 107species (Brako & Zarucchi, 1993), mostly vines and lianas. The family is under systematic revision, and these ongoing studies are likely to result in genus-level changes for the Peruvian Asclepiadaceae flora (S. Liede, pers. comm.). Given the scarcity of collections and the lack of consensus on the taxonomic status of several taxa, we provisionally recognize 43 endemic species. The endemic taxa are found in the Mesoandean and Very Humid Montane Forest regions, between 900 and 2600 m elevation. We applied IUCN categories and criteria to five species. Two endemic species have been found in protected areas.